The Evaluation of Arabic Learning based on Multiple Intelligences Classroom - Suci Ramadhanti Febriani; Rizka Widayanti (Postgraduate of IAIN Metro Lampung Indonesia, 2020)
Evaluation is an integral part of the curriculum component. Evaluation of language learning in general can provide an overview of student learning outcomes that have been done. The need for evaluation of Multiple Intelligences class-based learning evaluation techniques in order to expand the evaluation holistically according to the provisions of globalization. This study aims to analyze evaluation techniques based on Multiple Intelligences class at SD Plus Al-Kautsar Malang. This research using a qualitative approach through case study methods with data techniques include observation, interviews and documentation. This research shows evaluation techniques that can be developed in multiple intelligence classroom through several various techniques; portofolio services, personal expenses, projects. The research findings show that authority in authentic evaluation based on Multiple Intelligence classroom management can provide a concrete picture of students from the language skills system.